Measuring Organizational Capital in the New Economy - Sandra E. Black; Lisa M. Lynch (Institute for the Study of Labor (IZA), 2005)
A growing body of literature over the past decade suggests that a firm?s organizational structure/capital can contribute in significant ways to the productive capacity of a firm. But, as with other intangible assets, there is no consensus definition of what this organizational capital is, how to measure it, or how to best quantify its contribution to output (either current or future). We try to address this gap in the literature by proposing a definition of organizational capital based on recent empirical work on the impact of organizational capital on firm productivity and workers? wages. We then discuss in detail how organizational capital has been measured and the measurement issues that face those trying to understand the extent of organizational capital in an economy.
Keywords: D2; J2; 330; human capital; productivity; Unternehmensorganisation; Immaterielles Anlagevermögen; Organisationsstruktur; Messung; New Economy; Produktivität